Pemanfaatan Teh Celup Kombinasi Herbal sebagai Terapi Hipertensi pada Lansia di Desa Cigugur Girang - Uwan Purnama; Dinda Nazwa Maharani; Tika Nur Atikah; Nabila Nurul Habibah; Marcelin Kurniawati Hulu; M. Rifki Wildan Ansori (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Hypertension is widespread and constitutes a primary cause of mortality worldwide. Hypertension is a degenerative disease caused by uncontrolled lifestyle choices that lead to health problems and death. Age is a risk factor for hypertension and is common in older adults, due to decreased tissue elasticity and thickening, which ultimately increases cardiac output. The objective is to assess the efficacy of a blend of sambiloto, turmeric, and kencur herbal tea on the blood pressure of elderly people. This method was applied using an observational approach by measuring the blood pressure of 9 elderly respondents and residents of Cigugur Girang RW. 04 Village before and after consuming herbal tea containing extracts of sambiloto, turmeric, and kencur. Blood pressure measurements were taken using an aneroid sphygmomanometer after the respondents had rested to ensure they were relaxed. The data were recorded and analyzed descriptively to observe changes in blood pressure individually and in groups. The findings were analyzed to evaluate the efficacy of the herbal tea in lowering blood pressure as a preventive measure and treatment for hypertension. The assessment also considered various other aspects which could influence the outcomes, such as health status, eating habits, level of physical activity, and consistency in consuming herbal tea. This activity was part of a series of KKNT programs aimed at empowering the community through the use of natural ingredients.